Divergent properties and phylogeny of cyanobacterial 5‐enol‐pyruvyl‐shikimate‐3‐phosphate synthases: evidence for horizontal gene transfer in the Nostocales. Issue 1 (17th September 2014) - Forlani, Giuseppe; Bertazzini, Michele; Barillaro, Donatella; Rippka, Rosmarie
Summary: As it represents the target of the successful herbicide glyphosate, great attention has been paid to the shikimate pathway enzyme 5‐ enol ‐pyruvyl‐shikimate‐3‐phosphate (EPSP) synthase. However, inconsistent results have been reported concerning the sensitivity of the enzyme from cyanobacteria, and consequent inhibitory effects on cyanobacterial growth. The properties of EPSP synthase were investigated in a set of 42 strains representative of the large morphological diversity of these prokaryotes. Publicly available protein sequences were analyzed, and related to enzymatic features. In most cases, the native protein showed an unusual homodimeric composition and a general sensitivity to micromolar doses of glyphosate. By contrast, eight out of 15 Nostocales strains were found to possess a monomeric EPSP synthase, whose activity was inhibited only at concentrations exceeding 1 mM. Sequence analysis showed that these two forms are only distantly related, the latter clustering separately in a clade composed of diverse bacterial phyla. The results are consistent with the occurrence of a horizontal gene transfer event involving an evolutionarily distant organism. Moreover, data suggest that the existence of class I (glyphosate‐sensitive) and class II (glyphosate‐tolerant) EPSP synthases representing two distinct phylogenetic clades is an oversimplification because of the limited number of analyzed samples.